Формування життєвих траєкторій учнів інтернатних закладів на засадах компетентнісного підходу до освіти - Гордієнко, Наталія Миколаївна; Гордиенко, Наталья Николаевна; Hordiienko, Nataliia M. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано специфіку та позитивну динаміку формування в учнів трьох інтернатних закладів східної України їхніх життєвих траєкторій на засадах компетентнісного підходу до освіти шляхом застосування методики моніторингу рівня сформованості в школярів ключових життєвих компетенцій (В. Нечипоренко); визначено чинники ефективності цього процесу: використання сучасних освітньо-реабілітаційних технологій, організація особистісно зорієнтованого навчання, упровадження у виховний процес цільових життєтворчих програм, залучення учнів до соціальної та життєвої практики, функціонування системи учнівсько-студентського самоврядування, діяльність дитячого реабілітаційного театру. The article gives an analysis of the process and factors of the effective life-path formation of the children of boarding schools on the basis of competency-based approach. It is determined, that scientists use socio structure, subject and activity and institutional approaches to investigate life-path – the consistency of positions which the individual takes during his lifetime in different social situations. Special attention of the recent research is given to the problem of the social standing of the young people and their adaptation to the structure of society. There are represented the results of an empirical investigation of the process of life-courses formation in pupils of boarding schools, conducted in Zaporizhzhya and Dnepropetrovsk region, Ukraine. On the basis of the received findings it is identified that factors of life-courses forming under the conditions of boarding schools are: using of modern educational and rehabilitation technologies; person-centered approach in education; implementation to the educational process specialpurpose life-creative programs «I am the Person», «I am among the people», «I am the citizen of Ukraine», «I and Work», «I and Art», «I and Nature» for Elementary school, Middle school and High school; pupil participation in social and life practice under the educational and rehabilitation field; student self-governance system functioning on the basis of subject-subject relationship between all the participants of the educational process; activity of the pupils’ rehabilitation theatre with the possibility to found own repertoire for creative self-expression.
Life-path Forming of the Pupils of the Boarding Schools on the Basis of Competency-based Approach
Keywords: життєві траєкторії; учні інтернатних закладів; компетентнісний підхід; життєтворчі компетенції; life-path; boarding school students; competency approach; life-creative competency